Intellectual Property: Assessment of Additive Manufacturing as new Legal Category (Transactions on Additive Manufacturing Meets Medicine, 2019)
Patent Protection for Additive Manufacturing: Patent protection is available for methods and products as basic categories. Such a protection forms the basis of an injunctive relief for the owner of such inventive technologies embodied in these known and established categories. In most legal systems, a product is covered by a protected method if the product is an immediate and direct result of the protected method. However, additive manufacturing seems create a new category in the form of printing data as precursor of the product in view of the basic concept of this technology and the basic and general method of 3D-printing cannot properly reflect the specific properties of the resulting product.Legal Relationship: Printing Data and Resulting Object: According to the established case law, the infringement of a patent covering a product is strictly limited to the assessment of features of the alleged infringing product in view of the product claim. In earlier decisions, the “physicalness” of the result of a protected method as a requirement for reasonable and founded assessments of a patent infringement was contested. Future discussions in infringement courts will need to address the question if 3D printing data as precursor of products formed by additive manufacturing can be perceived as embodied teaching of a patented method or even of a patented product.